Isolation and algicidal properties study of the strain G1 from reservoir sediments - Keting Yuan; Qiong Wan; Dajun Ren; Beibei Chai; Aiqing Kang; Xiaohui Lei; Bin Chen (Water Supply, 2022)
Microcystis aeruginosa is a globally important cyanobacterial species that poses a threat to human health and development. The use of bacteria to control algal blooms has become an important research topic in recent years. In the present work, the algicidal strain G1 was isolated from sediments of a reservoir in Xi'an, China, identified by 16S ribosomal DNA (rDNA), and its algicidal effects were investigated. The rDNA sequence of G1 (GenBank accession number MW205793) is 99.86% similar to that of Chitinimonas sp., and the strain indirectly solubilised algae. Algae removal by G1 was optimal during the decay phase (algae solubilisation rate = 65.85%). Temperature (5–120 °C) did not significantly affect algae removal, pH 5–9 was tolerated, and pH 7 achieved the highest algae lysis rate (63.56%). Ultrasonic treatment of G1 destroyed the algae-solubilising effect. An injection ratio of 15% achieved the highest algae lysis rate (67.64%) under 12 h:12 h light:dark conditions, and full darkness achieved the highest algae lysis rate (68.21%). Thus, G1 can effectively inhibit the reproduction of M. aeruginosa, making it a promising biological agent for controlling algal growth. HIGHLIGHTS An algicidal bacterium strain G1 was isolated from source water reservoir sediment and identified as Chitinimonas.; G1 acts against Microcystis aeruginosa through indirect attack.; The active compound is heat stable.; Darkness, decay phase, and a 15% dosing ratio are optimal for algae solubilisation.;